2006
DOI: 10.1080/09670260600937791
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic characteristics of the phytoplankton in the Scheldt estuary: community and single-cell fluorescence measurements

Abstract: Estuaries present a very dynamic environment for phytoplankton with large changes in salinity occurring over relatively short distances, usually with high turbidity. We investigated the photosynthetic characteristics of phytoplankton in the Scheldt estuary (Belgium and the Netherlands) along a salinity gradient using community and single-cell fluorescence measurements. Single-cell fluorescence measurements offer the opportunity to study differences between species that were formerly possible only using uni-alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Some studies indicate that changes in phytoplankton community structure may lead to differential response to FRRF (Moore et al 2005;Suggett et al 2009a); therefore, such information would have improved the interpretation of our findings. On the other hand, other studies have shown that there are only small differences in F v /F m between different species in estuarine settings (Dijkman and Kronkamp 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Some studies indicate that changes in phytoplankton community structure may lead to differential response to FRRF (Moore et al 2005;Suggett et al 2009a); therefore, such information would have improved the interpretation of our findings. On the other hand, other studies have shown that there are only small differences in F v /F m between different species in estuarine settings (Dijkman and Kronkamp 2006).…”
Section: Discussionmentioning
confidence: 98%
“…However, the maintenance of high F v /F m values even during the decline phase of the cultures is unexpected and surprising since F v /F m is commonly used as an indicator of the physiological state of cells, which responds mostly to nutrient limitation and high irradiance (Kolber and Falkowski, 1993). Because large proportions of dead "but intact and pigment-containing" cells are now known to be present in phytoplankton communities (Veldhuis et al, 2001;Agustí 2004), Franklin et al (2009) (Dijkman and Kromkamp, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, changes in salinity have been less studied in benthic diatoms, while in planktonic diatoms it is known to induce modification of community species diversity (Dijkman and Kromkamp, 2006;Muylaert et al, 2009;Petrou et al, 2011;Thessen et al, 2005), and of growth and photosynthesis (Dijkman and Kromkamp, 2006;Petrou et al, 2011;Thessen et al, 2005). Salinity often co-varies with other environmental gradients like light and temperature in the case of high salinities (due to pore-water evaporation in the upper-layer of the sediment) and with nutrient concentrations in the case of low salinities (due to the discharge of estuarine rivers) (Admiraal and Peletier, 1980;Thornton et al, 2002;Underwood and Provot, 2000).…”
Section: Introductionmentioning
confidence: 99%